SIFAT MEKANIK KOMPOSIT ARANG AKTIF BERBAHAN DASAR LIMBAH CANGKANG KEMIRI DAN RESIN EPOKSI - Pratiwi, Putri; Nurzal, Nurzal; Hafni, Hafni; Perdana, Mastariyanto (ITP Press, 2026)
This study investigates the effect of weight fraction in an epoxy-based composite reinforced with candlenut shell charcoal powder on mechanical properties, specifically shear strength and flexural strength. The filler consisted of candlenut shell charcoal powder with a particle size of 841 to 1190 μm. The candlenut shell charcoal to epoxy matrix ratios were varied at 55:45 %wt, 60:40 %wt, 65:35 %wt, 70:30 %wt, 75:25 %wt, 80:20 %wt, and 85:15 %wt. Composite specimens were prepared by homogeneous mixing, molding, and followed by room-temperature curing before mechanical testing. Mechanical characterization was conducted through flexural and shear tests using a Universal Testing Machine (UTM) with appropriate fixtures for each test method. The results indicate that increasing the filler fraction tends to reduce the mechanical performance of the composites. The highest flexural strength was obtained at 55:45 %wt by 16.63 MPa, while the lowest value was recorded at 85:15 %wt by 4.88 MPa. The highest shear strength also occurred at 55:45 %wt by 8.87 MPa and reached the minimum at 80:20 %wt by approximately 1.65 MPa, with a sharp decrease observed at 70:30 %wt. Overall, the findings demonstrate that increasing the candlenut shell charcoal powder fraction decreases both flexural and shear strengths. This degradation at high filler loadings is associated with reduced epoxy wetting of particles, increased agglomeration and porosity, and weakened load transfer across the filler–matrix interface. These results suggest that the composite formulation requires an optimum filler fraction and careful control of mixing and molding processes to achieve more stable mechanical performance.